2021
DOI: 10.1021/acs.cgd.1c01140
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Studies of Aromatic Guests in Three Isostructural Inclusion Compounds with Molecular Boron–Nitrogen Hosts

Abstract: The dynamics of three guests: benzene (ben), naphthalene (nap), and xylene (xyl) included in the isostructural cavities of tetrameric [(2fbe) 2 (bpy)⊃guest] 4 cages were examined using single-crystal X-ray diffraction, thermogravimetric analysis, variable-temperature solid-state 2 H NMR spectroscopy, and molecular dynamics simulations. The inclusion compounds were selected from a series of boron−nitrogen host adducts assembled in a 2:1 stoichiometric ratio from the catechol ester of 2,4difluorophenylboronic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…[30][31][32] The utilization of dative B)N bonds in structural supramolecular chemistry has become increasingly popular in recent years. [33][34][35] Since Kay Severin pioneered the synthesis of the rst crystalline organic framework based on the B)N bonds (BNOF) by using triboronate esters and bipyridyl ligands in 2011, 36 other 1D and 2D crystalline BNOFs have been designed and synthesized by combining polytopic N-donor ligands with polyboronate esters. [37][38][39] It is now known that the robustness of B)N bonds is signicantly dependent upon the steric and electronic properties of the interacting components, 33,40 as these properties can prevent the sensitive boronate ester moieties from hydrolyzing.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32] The utilization of dative B)N bonds in structural supramolecular chemistry has become increasingly popular in recent years. [33][34][35] Since Kay Severin pioneered the synthesis of the rst crystalline organic framework based on the B)N bonds (BNOF) by using triboronate esters and bipyridyl ligands in 2011, 36 other 1D and 2D crystalline BNOFs have been designed and synthesized by combining polytopic N-donor ligands with polyboronate esters. [37][38][39] It is now known that the robustness of B)N bonds is signicantly dependent upon the steric and electronic properties of the interacting components, 33,40 as these properties can prevent the sensitive boronate ester moieties from hydrolyzing.…”
Section: Introductionmentioning
confidence: 99%
“…Dative B ← N bonds are widely acknowledged for their role in constructing supramolecular structures. Although B ← N bonds can be stronger than hydrogen bonds, their capacity to create permanent porosity in frameworks has only been confirmed recently. We refer to such materials as B ← N frameworks (BNF). , In previous studies, we observed significant electron transfer between N- and B-containing monomers during the formation of B ← N bonds. This process endows the N-containing monomers with obvious electron-deficient features, thereby creating specific binding sites for aromatic compounds, such as Tol. , However, the separation of Tol from mixtures has not been achieved in B ← N materials to date. The crystalline and stable BNFs are very rarely obtained especially under the condition of mixed organic solvents, which make it arduous to build up frameworks for highly selective recognition and separation of aromatic hydrocarbons from mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…The design of molecular rotation in crystalline media has attracted much interest not only in the field of molecular machines but also in solid-state functional materials, because the rotation-induced molecular geometry alteration can provide an avenue for switching the physical properties of solid compounds. [1][2][3][4][5][6][7][8] To construct the crystalline materials, known as crystalline molecular rotors, gyroscope-like molecular rotors, [2][3][4][9][10][11] dumbbell-shaped molecules, [2][3][12][13][14][15][16][17] and porous solid-state materials such as metal-organic frameworks (MOFs) [5][6][7][8][18][19][20][21][22][23] have been utilized. The general blueprint of this design is based on the combination of a rotator moiety with a bulky and rigid domain as a stator that is used to construct the ordered frame as well as the local space that can undergoes molecular rotation.…”
Section: Introductionmentioning
confidence: 99%